High-dispersion ruthenium-loaded cerium-zirconium solid solution photocatalyst, preparation method and application thereof in hydrogen production by photocatalytic ammonia decomposition at room temperature

Through the highly dispersed ruthenium-supported cerium-zirconium solid solution photocatalyst, the problem of low hydrogen production rate and high energy consumption of ammonia decomposition hydrogen production catalyst under low temperature conditions is solved, and high efficiency photocatalyzed ammonia decomposition hydrogen production at room temperature is achieved, breaking through the thermodynamic limitations.

CN119608157AInactive Publication Date: 2025-03-14JILIN UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411812105.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing ammonia decomposition hydrogen production catalysts have problems such as excessive reaction temperature, low hydrogen production rate and high energy consumption under low temperature conditions, and the catalytic efficiency and selectivity of cerium-zirconium composite oxides in this direction are insufficient.

Method used

A cerium-zirconium solid solution precursor is prepared by mixing cerium-zirconium salt and zirconium salt with a reducing agent, and ruthenium solid solution precursor is supported by calcining and impregnation to form a highly dispersed ruthenium-supported cerium-zirconium solid solution photocatalyst.

Benefits of technology

At room temperature, the use of visible light irradiation significantly improves the conversion efficiency of hydrogen produced by ammonia decomposition, breaks through the thermodynamic limitations, and improves catalytic activity and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608157A_ABST
    Figure CN119608157A_ABST
Patent Text Reader

Abstract

The invention discloses a high-dispersion ruthenium-loaded cerium-zirconium solid solution photocatalyst, a preparation method and application of the photocatalyst in hydrogen production by photocatalytic ammonia decomposition at room temperature, and belongs to the technical field of hydrogen production by photocatalytic ammonia decomposition. The preparation method comprises the following steps: preparing a cerium-zirconium solid solution precursor from cerium salt and zirconium salt as raw materials, grinding into powder, calcining at high temperature to obtain a cerium-zirconium solid solution, dispersing in deionized water, dropwise adding a ruthenium precursor solution and a reducing agent, and performing reduction reaction to obtain a ruthenium-loaded cerium-zirconium solution; and carrying out suction filtration, drying and grinding to obtain the high-dispersion ruthenium-loaded cerium-zirconium solid solution photocatalyst. The photocatalyst can be applied to hydrogen production by photocatalytic ammonia decomposition at room temperature. According to the photocatalyst disclosed by the invention, the conversion efficiency of hydrogen prepared by ammonia gas decomposition at room temperature under visible light irradiation is improved, the thermodynamic limitation of the reaction is greatly broken through, the hydrogen production rate of ammonia decomposition reaches 56.12 mmol H2gcat <-1 > min <-1 >, and the ammonia gas conversion rate reaches 74.83%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photocatalytic ammonia decomposition to produce hydrogen, and specifically relates to a highly dispersed ruthenium-loaded cerium-zirconium solid solution photocatalyst, a preparation method and application thereof in room temperature photocatalytic ammonia decomposition to produce hydrogen. Background Art

[0002] Hydrogen is a green renewable energy source with no pollution and no carbon dioxide emissions. Using hydrogen energy is an effective way to achieve carbon peak and carbon neutrality. Because the only product of hydrogen combustion is water, no CO is emitted. x , which has obvious advantages over other traditional energy sources. However, the storage and transportation of hydrogen brings us great challenges. First, the transported hydrogen requires very low temperature and high pressure, which not only brings huge energy consumption, but also puts high demands on storage materials. Secondly, the diffusion of hydrogen in the container will make the material brittle and weak, and the use of transportable compounds to store hydrogen and release hydrogen through chemical reactions is considered a practical method.

[0003] Ammonia has a high hydrogen storage capacity (17.7 wt% H 2 ) and high energy density, easy liquefaction and storage under mild conditions (20°C, 0.8MPa), and annual production of one billion tons. Therefore, ammonia is considered to be a promising hydrogen carrier. 3 Converted to carbon-free H 2 , solving the problems of hydrogen storage, transportation decarbonization and NH 3 The key to realizing these applications lies in the design and synthesis of efficient ammonia decomposition catalysts.

[0004] At present, the catalysts used for hydrogen production by ammonia decomposition generally have the problems of too high a temperature required for ammonia decomposition, low hydrogen production rate under low temperature conditions, and high energy consumption. A large number of studies have shown that transition metal catalysts have significant catalytic activity for ammonia decomposition reactions, and the order of metal catalytic activity is Ru>Ni>Rh>Co>Ir>Fe>Pt>Cr>Pd>Cu. Cerium-zirconium composite oxides are favored in many catalytic fields due to their high specific surface area and abundant oxygen vacancies, but there is still room for exploration in the direction of hydrogen production by ammonia decomposition. Therefore, the present invention selects ruthenium as the active metal and uses cerium-zirconium solid solution as the carrier of the active metal to explore its role in the ammonia decomposition reaction, further enhance the catalytic activity of the catalyst, and improve the catalytic efficiency and selectivity of the ammonia decomposition hydrogen production reaction, thereby promoting the development of the clean energy field. Summary of the invention

[0005] In order to achieve efficient photocatalytic ammonia decomposition to produce hydrogen reaction, the present invention provides a highly dispersed ruthenium-loaded cerium-zirconium solid solution photocatalyst, a preparation method and its application in room temperature photocatalytic ammonia decomposition to produce hydrogen.

[0006] The method for preparing a highly dispersed ruthenium-loaded cerium-zirconium solid solution photocatalyst described in the present invention comprises the following steps:

[0007] (1) Mixing cerium salt, zirconium salt and reducing agent in a certain proportion, dissolving them in an evaporating dish under stirring, heating and evaporating the solvent, and then heating to induce a spontaneous combustion reaction to obtain a cerium-zirconium solid solution precursor; or preparing the cerium-zirconium solid solution precursor by a chemical precipitation method, which is to weigh a certain proportion of cerium salt and zirconium salt and dissolve them in deionized water, then drop an alkaline solution and stir to make them fully react to generate a metal hydroxide precipitate, and then wash with distilled water and anhydrous ethanol respectively under high-speed centrifugation to remove impurities, and then dry to obtain a cerium-zirconium solid solution precursor; the cerium salt is one of hexahydrated cerium nitrate, cerium acetate, and heptahydrated cerium chloride; the zirconium salt is zirconium nitrate pentahydrate, zirconium oxynitrate dihydrate, zirconium oxychloride octahydrate, or zirconium nitrate pentahydrate. one of the following; the reducing agent is one of glycine, oxalic acid and citric acid; the alkaline solution is one of potassium hydroxide solution, sodium hydroxide solution, cesium hydroxide solution and ammonia solution, and the concentration of the alkaline solution is 1-6 mol / L; the molar amounts of cerium salt, zirconium salt and reducing agent are represented by x, y and z, (x+y):z=1:1; the temperature for evaporating the solvent is 90-110°C, and the temperature for initiating the natural reaction is 130-300°C; the speed of the high-speed centrifugation is 10000-15000 r / min, and the time of the high-speed centrifugation is 3-5 min; the number of washings with distilled water and anhydrous ethanol is 2-3 times respectively; the drying is vacuum drying at room temperature for 12-24 hours;

[0008] (2) grinding the cerium-zirconium solid solution precursor obtained in step (1) into powder, and then transferring it to a muffle furnace for high-temperature calcination to obtain a cerium-zirconium solid solution; the high-temperature calcination is carried out in an air atmosphere, heating to 600-700° C. at a rate of 3-6° C. / min and calcining for 3-5 hours;

[0009] (3) Weigh the cerium-zirconium solid solution powder in step (2) and disperse it in deionized water, then drop a ruthenium precursor solution, drop a reducing agent while stirring, and obtain a ruthenium-loaded cerium-zirconium solution after a reduction reaction; the ruthenium precursor solution is RuCl 3 、Ru(CH 3 COO 3 , C 15 H 21 O 6 Ru, Ru 3 (CO) 12 The mass concentration of ruthenium in the ruthenium precursor solution is 0.1-20 mg / mL; the mass percentage of ruthenium loaded is 0.1-5% based on the mass of the cerium-zirconium solid solution; the reducing agent is NaBH 4 , NaBH 4 Mixture of NaOH, LiH, LiHCO 3One of the methods, wherein the mass ratio of the reducing agent to the cerium-zirconium solid solution powder is 0.8-1.2:1, and the stirring is performed by magnetic stirring at 500-1000 r / min for 3-4 hours;

[0010] (4) filtering, drying, and grinding the ruthenium-loaded cerium-zirconium solution obtained in step (3) to obtain a highly dispersed ruthenium-loaded cerium-zirconium solid solution photocatalyst; the filtration is to filter the ruthenium-loaded cerium-zirconium solution with a water pump and wash it with deionized water for 3 to 5 times; the drying is to vacuum dry it at room temperature for 12 to 24 hours.

[0011] Unless otherwise specified, the solvents used in the present invention are all deionized water.

[0012] The invention also relates to a highly dispersed ruthenium-loaded cerium-zirconium solid solution photocatalyst, which is prepared by the above method.

[0013] The present invention also relates to the application of a cerium-zirconium solid solution photocatalyst loaded with highly dispersed ruthenium in photocatalytic ammonia decomposition and hydrogen production at room temperature. The room temperature range is 20-25°C; the light source of the photocatalyst is visible light with a wavelength range of 400nm-2500nm.

[0014] The application of the ruthenium-loaded cerium-zirconium solid solution photocatalyst in room temperature photocatalytic ammonia decomposition to produce hydrogen is specifically characterized by placing the synthesized ruthenium-loaded cerium-zirconium solid solution catalyst in a gas phase reactor, controlling the reaction at room temperature by a constant temperature water bath, and then adding NH 3 Use a gas-tight needle to inject into the reactor, add a JB400 filter above the reactor, and then use visible light to irradiate the JB400 filter above the gas phase reactor to react, thereby obtaining the product hydrogen; then inject dilute sulfuric acid into the reactor to neutralize the unreacted NH 3 , and then quantitatively calculate H 2 The yield and NH 3 conversion rate.

[0015] The advantages of the present invention compared with the prior art are:

[0016] (1) The present invention uses soluble cerium salt and zirconium salt as precursors and then treats them with glycine, oxalic acid, citric acid, etc. to synthesize a cerium-zirconium solid solution with a high specific surface area and abundant oxygen vacancies, and improves the catalyst on this basis; then the active component ruthenium is loaded by an impregnation method, the component content is easy to control, the repeatability is high, and the problem of low content and poor dispersibility of the active component in the catalyst is solved;

[0017] (2) The highly dispersed ruthenium-loaded cerium-zirconium solid solution photocatalyst of the present invention solves the problems of high reaction temperature (≥500°C), low conversion efficiency, high energy consumption, poor thermal stability, and inability to achieve efficient decomposition of ammonia in the previous process of hydrogen production by decomposition of ammonia;

[0018] (3) The photocatalyst synthesis steps of the present invention are simple, deionized water is mostly used as the solvent in the preparation process, the pollution is small, the equipment requirements are not high, and the reaction conditions are mild and easy to achieve;

[0019] (4) The photocatalyst in the present invention is used for the first time to photocatalytically decompose ammonia to produce hydrogen. At room temperature (20-25°C) and under the irradiation of visible light (λ≥400nm), the conversion efficiency of ammonia decomposition to produce hydrogen is improved, which greatly breaks through the thermodynamic limitations of the reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The figures are the powder X-ray diffraction spectra of the cerium-zirconium solid solution products obtained in Examples 1, 8, 9, 10 and 11 of the present invention; the comparison with the standard cards of cerium oxide and zirconium oxide proves that the cerium-zirconium solid solution is synthesized; no obvious ruthenium peak is observed in the samples loaded with different mass percentages of ruthenium, and the position of the diffraction peak is not significantly shifted, indicating that the dispersion degree of ruthenium is high;

[0021] Figure 2 The transmission electron microscope photo (a), particle size distribution bar graph (b) and lattice fringe graph (c) of the cerium-zirconium solid solution (CZ) synthesized in Example 1 show that the particle size is about 4.7 nm and the sample has good crystallinity.

[0022] Figure 3 This is the SEM-EDS image of the 5% Ru-CZ product obtained in Example 1; it can be seen that the product contains cerium, zirconium and ruthenium elements, proving that ruthenium is indeed doped into the cerium-zirconium solid solution;

[0023] Figure 4 The CeO obtained in Example 1 and Example 2 2 , CZ, and 5%Ru-CZ samples; it can be seen that CeO 2 The luminescence intensity of and CZ is higher than that of Ru-CZ, indicating that the addition of oxygen vacancies and ruthenium effectively reduces the recombination rate of photogenerated carriers;

[0024] Figure 5 The CeO obtained in Example 1 2 The XPS test data of oxygen elements in CZ show that the XPS peak area of ​​vacancy oxygen increases with the addition of zirconium.

[0025] Figure 6The XRD spectra of cerium-zirconium solid solutions synthesized using different cerium-zirconium ratios in Examples 1 to 7 (left figure) and the bar graph of the yield of hydrogen generated by direct decomposition of cerium-zirconium solid solution photocatalysts synthesized using different cerium-zirconium ratios in ammonia and the conversion rate of ammonia (right figure); From the XRD spectra, it can be seen that the peak shapes are consistent, indicating that the doping of Zr atoms does not cause changes in the crystal structure of cerium oxide, so these seven samples show completely consistent XRD characteristic peaks. As the Zr ratio increases, the position of the diffraction peak obviously shifts to a high angle. This is mainly because the ionic radius of the Ce element is slightly larger than that of the Zr element, and the introduction of the Zr element leads to the CeO 2 The crystal shrinks. As can be seen from the right figure, as the proportion of Ce atoms increases, H 2 Yield and NH 3 The conversion rate first increases and then decreases. When the ratio of cerium to zirconium is 1:1, the ammonia decomposition hydrogen production rate and ammonia conversion rate reach the highest.

[0026] Figure 7 The figure is a bar graph of the yield of hydrogen generated by direct decomposition of photocatalysts loaded with different ruthenium contents in ammonia (left ordinate) and the conversion rate of ammonia (right ordinate) in Examples 1, 8, 9, 10, and 11. It can be seen that the photocatalytic hydrogen production performance of ammonia loaded with 5% ruthenium is the best; the catalyst has good catalytic activity and stability, and the ammonia decomposition hydrogen production rate reaches 56.12 mmol H at room temperature and visible light irradiation. 2 gcat -1 min -1 , the ammonia conversion rate reached 74.83%. DETAILED DESCRIPTION

[0027] The following examples are given to further describe the present invention in detail. The specific operation process in the examples can enable those skilled in the art to understand the present invention more comprehensively. However, the examples do not constitute a limitation of the present invention.

[0028] Embodiment 1:

[0029] (1) Prepare a 50 mL beaker and weigh 4.34 g (0.01 mol) of Ce(NO 3 ) 3 6H 2 O, 2.31 g (0.01 mol) of ZrO (NO 3 ) 2and 1.5g (0.02mol) of glycine, dispersed in 20mL of deionized water and stirred for 30min at a speed of 600r / min. The solution was then transferred to a 300mL evaporating dish, heated to 90℃ to evaporate the solvent, and then heated to 200℃. The sample reacted by exothermic self-ignition through redox reaction; the obtained cerium-zirconium solid solution precursor was then transferred to a muffle furnace, heated to 650℃ at 5℃ / min and calcined for 4h to obtain a cerium-zirconium solid solution powder, named CZ. X-ray diffraction (XRD) was performed on it, and the results are shown in Figure 1 ;

[0030] (2) Weigh 100 mg of the cerium-zirconium solid solution (CZ) powder prepared in step (1), transfer it to a 100 mL beaker, add 50 mL of deionized water, place it on a stirring table, and stir at a speed of 600 r / min for 30 min to obtain a cerium-zirconium solid solution solution;

[0031] (3) using deionized water as solvent, preparing a ruthenium chlorate solution with a ruthenium ion mass concentration of 20 mg / mL, and using a pipette to transfer 250 μL of the ruthenium chlorate solution into the cerium-zirconium solid solution solution obtained in step (2);

[0032] (4) Weigh 100 mg NaBH 4 In a small beaker, add 5 mL of deionized water, ultrasonicate to dissolve it completely, use a common dropper to slowly drip the sodium borohydride solution into the solution of step (3), and drip it completely in about 10 minutes. After stirring for another 1 hour, filter with a water pump and wash with deionized water 4 times, put it in a vacuum drying oven at room temperature for 20 hours, and grind to obtain about 150 to 200 mg of highly dispersed ruthenium-loaded cerium-zirconium solid solution photocatalyst. Among them, based on the mass of the cerium-zirconium solid solution catalyst, the mass percentage of loaded ruthenium is 5%, and the catalyst is named 5% Ru-CZ.

[0033] (5) Weigh 10 mg of the ruthenium-loaded cerium-zirconium solid solution photocatalyst in step (4), dissolve it with an appropriate amount of deionized water, disperse it by ultrasound, and spread it on the filter membrane with a dropper. After drying completely under an infrared lamp, put the filter membrane with the catalyst back into the bottom of the quartz reactor, evacuate it with a pump to make it in a closed state, and then transfer it to an electric thermostatic reactor and activate it under vacuum conditions at 200° C. for 30 minutes. After the quartz reactor is cooled to room temperature, the hose is clamped and removed, and 500 μmol NH 3Beat it into a quartz reactor. Then put it in a constant temperature water bath to control the temperature of the reactor. A xenon lamp is placed above the quartz reactor as a light source to irradiate the photocatalytic ammonia decomposition and hydrogen production reaction. During the reaction, the working current of the xenon lamp can be adjusted to change the intensity of light, and the xenon lamp can be equipped with filters of different wavelengths to change the irradiation range. After the photocatalytic reaction is completed, an appropriate amount of dilute sulfuric acid is injected into the quartz reactor to neutralize the unreacted ammonia. Then, a gas-tight needle is used to extract the gas from the quartz reactor, and each gas component is detected by gas chromatography. The hydrogen production rate of ammonia decomposition reached 56.12mmol H2 gcat-1min-1, and the ammonia conversion rate reached 74.83%. The results are shown in Figure 6 (Right picture).

[0034] Calculate H 2 The yield and NH 3 The operation of the conversion meter is as follows: First, make a H 2 Specifically, different amounts of H 2 , the gas chromatograph GC will display the corresponding hydrogen peak area. 2 The corresponding relationship between the amount of substance and the standard curve of hydrogen are drawn. 2 The yield is obtained by first obtaining the hydrogen peak area displayed on the GC chromatogram according to the reaction, calculating the corresponding amount of hydrogen substance through the hydrogen standard curve made earlier, and then dividing it by the mass of the catalyst used and the reaction time to get H 2 The yield of the reaction NH 3 The amount of substance divided by the total NH 3 The amount of substance is NH 3 conversion rate.

[0035] Embodiment 2:

[0036] The preparation and reaction were carried out using the method of Example 1, except that in step (1), only 8.682 g (0.02 mol) of Ce(NO 3 ) 3 6H 2 O, and the remaining steps are not performed. The catalyst synthesized by this method is named CeO 2 , and the results of X-ray diffraction (XRD) are shown in Figure 6 (Left figure). The hydrogen production rate of ammonia decomposition reached 30.13mmol H 2 gcat -1 min -1 , the ammonia conversion rate reached 40.17%, the results are shown in Figure 6 (Right picture).

[0037] Embodiment 3:

[0038] The preparation and reaction were carried out using the method of Example 1, except that in step (1), only 4.624 g (0.02 mol) of ZrO(NO) was weighed. 3 ) 2 The remaining steps are not performed. The catalyst synthesized by this method is named ZrO 2 , and the results of X-ray diffraction (XRD) are shown in Figure 6 (Left picture). The hydrogen production rate of ammonia decomposition reached 1.28mmol H 2 gcat -1 min -1 , the ammonia conversion rate reached 1.7%, the results are shown in Figure 6 (Right picture).

[0039] Embodiment 4:

[0040] The preparation and reaction were carried out using the method of Example 1, except that in step (1), 0.868 g (0.002 mol) of Ce(NO 3 ) 3 6H 2 O, 4.16 g (0.018 mol) of ZrO (NO 3 ) 2 The catalyst synthesized by this method is named 5%Ru-C 1 Z 9 , and the results of X-ray diffraction (XRD) are shown in Figure 6 (Left picture). The hydrogen production rate of ammonia decomposition reaches 3.20mmolH 2 gcat -1 min -1 , the ammonia conversion rate reached 4.27%, the results are shown in Figure 6 (right graph), which is lower than the data in Example 1.

[0041] Embodiment 5:

[0042] The preparation and reaction were carried out using the method of Example 1, except that in step (1), 2.605 g (0.006 mol) of Ce(NO 3 ) 3 6H 2 O, 3.237 g (0.014 mol) of ZrO (NO 3 ) 2 The catalyst synthesized by this method is named 5%Ru-C 3 Z 7 , and the results of X-ray diffraction (XRD) are shown in Figure 6 (Left picture). The hydrogen production rate of ammonia decomposition reached 15.27mmolH 2 gcat -1 min-1 , the ammonia conversion rate reached 20.37%, the results are shown in Figure 6 (right graph), which is lower than the data in Example 1.

[0043] Embodiment 6:

[0044] The preparation and reaction were carried out by the method of Example 1, except that in step (1), 6.078 g (0.014 mol) of Ce(NO 3 ) 3 6H 2 O, 1.387 g (0.006 mol) of ZrO (NO 3 ) 2 The catalyst synthesized by this method is named 5%Ru-C 7 Z 3 , and the results of X-ray diffraction (XRD) are shown in Figure 6 (Left picture). The hydrogen production rate of ammonia decomposition reached 36.52mmolH 2 gcat -1 min -1 , the ammonia conversion rate reached 48.70%, the results are shown in Figure 6 (right graph), which is lower than the data in Example 1.

[0045] Embodiment 7:

[0046] The preparation and reaction were carried out using the method of Example 1, except that in step (1), 7.814 g (0.018 mol) of Ce(NO 3 ) 3 6H 2 O, 0.4625 g (0.002 mol) of ZrO (NO 3 ) 2 The catalyst synthesized by this method is named 5%Ru-C 9 Z 1 , and the results of X-ray diffraction (XRD) are shown in Figure 6 (Left picture). The hydrogen production rate of ammonia decomposition reached 38.23mmol H 2 gcat -1 min -1 , the ammonia conversion rate reached 50.98%, the results are shown in Figure 6 (right graph), which is lower than the data in Example 1.

[0047] Embodiment 8:

[0048] The method of Example 1 was used for preparation and reaction, except that 5 μL of ruthenium chlorate solution was pipetted with a pipette in step (3), and the mass percentage of ruthenium supported was 0.1% based on the mass of the cerium-zirconium solid solution catalyst. The catalyst synthesized by this method was named 0.1%Ru-CZ, and X-ray diffraction (XRD) was performed on it. The results are shown in FIG. Figure 1 The hydrogen production rate of ammonia decomposition reached 5.26mmol H 2 gcat -1 min -1 , the ammonia conversion rate reached 7.02%, the results are shown in Figure 7 .

[0049] Embodiment 9:

[0050] The method of Example 1 was used for preparation and reaction, except that 25 μL of ruthenium chlorate solution was pipetted with a pipette in step (3), and the mass percentage of ruthenium supported was 0.5% based on the mass of the cerium zirconium solid solution catalyst. The catalyst synthesized by this method was named 0.5% Ru-CZ, and X-ray diffraction (XRD) was performed on it. The results are shown in FIG. Figure 1 The hydrogen production rate of ammonia decomposition reached 8.17 mmol H 2 gcat -1 min -1 , the ammonia conversion rate reached 10.89%, the results are shown in Figure 7 .

[0051] Embodiment 10:

[0052] The method of Example 1 was used for preparation and reaction, except that 50 μL of ruthenium chlorate solution was pipetted with a pipette in step (3), and the mass percentage of ruthenium supported was 1% based on the mass of the cerium zirconium solid solution catalyst. The catalyst synthesized by this method was named 1%Ru-CZ, and X-ray diffraction (XRD) was performed on it. The results are shown in FIG. Figure 1 The hydrogen production rate of ammonia decomposition reached 18.78mmol H 2 gcat -1 min -1 , the ammonia conversion rate reached 25.04%, the results are shown in Figure 7 .

[0053] Embodiment 11:

[0054] The method of Example 1 was used for preparation and reaction, except that 150 μL of ruthenium chlorate solution was pipetted with a pipette in step (3), and the mass percentage of ruthenium supported was 3% based on the mass of the cerium zirconium solid solution catalyst. The catalyst synthesized by this method was named 3%Ru-CZ, and X-ray diffraction (XRD) was performed on it. The results are shown in FIG. Figure 1 The hydrogen production rate of ammonia decomposition reached 44.46mmol H2 gcat -1 min -1 , the ammonia conversion rate reached 59.28%, the results are shown in Figure 7 .

Claims

1. A method for preparing a highly dispersed ruthenium-loaded cerium-zirconium solid solution photocatalyst, the steps of which are as follows: (1) Mixing cerium salt, zirconium salt and reducing agent in a certain proportion, stirring and dissolving them in an evaporating dish, heating and evaporating the solvent, and then heating to induce a spontaneous combustion reaction to obtain a cerium-zirconium solid solution precursor; or weighing a certain proportion of cerium salt and zirconium salt and dissolving them in deionized water, then dropping an alkaline solution and stirring to make them fully react to generate a metal hydroxide precipitate, and then washing with distilled water and anhydrous ethanol respectively under high-speed centrifugation to remove impurities, and drying to obtain a cerium-zirconium solid solution precursor; the molar amounts of cerium salt, zirconium salt and reducing agent are represented by x, y, and z, (x+y):z=1:1; (2) grinding the cerium-zirconium solid solution precursor obtained in step (1) into powder, and then transferring it to a muffle furnace for high-temperature calcination to obtain a cerium-zirconium solid solution; (3) Weighing the cerium-zirconium solid solution powder in step (2) and dispersing it in deionized water, then dropping a ruthenium precursor solution, adding a reducing agent while stirring, and obtaining a ruthenium-loaded cerium-zirconium solution after a reduction reaction; the mass concentration of ruthenium in the ruthenium precursor solution is 0.1 to 20 mg / mL; the mass percentage of loaded ruthenium is 0.1 to 5% based on the mass of the cerium-zirconium solid solution; the mass ratio of the reducing agent to the cerium-zirconium solid solution powder is 0.8 to 1.2:1; (4) The ruthenium-loaded cerium-zirconium solution obtained in step (3) is filtered, dried, and ground to obtain a highly dispersed ruthenium-loaded cerium-zirconium solid solution photocatalyst.

2. The method for preparing a highly dispersed ruthenium-loaded cerium-zirconium solid solution photocatalyst according to claim 1, characterized in that: The cerium salt described in step (1) is one of cerium nitrate hexahydrate, cerium acetate, and cerium chloride heptahydrate; the zirconium salt is one of zirconium nitrate pentahydrate, zirconium oxynitrate dihydrate, and zirconium oxychloride octahydrate; the reducing agent is one of glycine, oxalic acid, and citric acid; the alkaline solution is one of potassium hydroxide solution, sodium hydroxide solution, cesium hydroxide solution, and ammonia solution, and the concentration of the alkaline solution is 1 to 6 mol / L.

3. The method for preparing a highly dispersed ruthenium-loaded cerium-zirconium solid solution photocatalyst according to claim 1, characterized in that: In step (1), the temperature for evaporating the solvent is 90-110° C., the temperature for initiating natural drying is 130-300° C.; the speed of high-speed centrifugation is 10000-15000 r / min, and the time of high-speed centrifugation is 3-5 min; the number of washing with distilled water and anhydrous ethanol is 2-3 times respectively; and the drying is vacuum drying at room temperature for 12-24 h.

4. The method for preparing a highly dispersed ruthenium-loaded cerium-zirconium solid solution photocatalyst according to claim 1, characterized in that: In step (2), the high temperature calcination is carried out in an air atmosphere by heating the material to 600-700° C. at a rate of 3-6° C. / min and calcining the material for 3-5 hours.

5. The method for preparing a highly dispersed ruthenium-loaded cerium-zirconium solid solution photocatalyst according to claim 1, characterized in that: The ruthenium precursor solution in step (3) is RuCl3, Ru(CH3COO)3, C 15 H 21 O6Ru、Ru3(CO) 12 The reducing agent is one of NaBH4, a mixture of NaBH4 and NaOH, LiH, and LiHCO3. The stirring is magnetic stirring at 500-1000 r / min for 3-4 hours.

6. The method for preparing a highly dispersed ruthenium-loaded cerium-zirconium solid solution photocatalyst according to claim 1, characterized in that: The filtration described in step (4) is to filter the ruthenium-loaded cerium-zirconium solution with a water pump and wash it with deionized water for 3 to 5 times; the drying is vacuum drying at room temperature for 12 to 24 hours.

7. A highly dispersed ruthenium-loaded cerium-zirconium solid solution photocatalyst, characterized in that: The method is prepared by any one of claims 1 to 6.

8. Use of the highly dispersed ruthenium-loaded cerium-zirconium solid solution photocatalyst as claimed in claim 7 in room temperature photocatalytic ammonia decomposition to produce hydrogen.

9. The use of a highly dispersed ruthenium-loaded cerium-zirconium solid solution photocatalyst as claimed in claim 8 in room temperature photocatalytic ammonia decomposition to produce hydrogen, characterized in that: Room temperature refers to the condition of 20-25°C; the light source is visible light with a wavelength range of 400nm-2500nm.

Citation Information

Patent Citations

  • Method for preparing and applying ruthenium-supported cerium-zirconium-based catalyst

    CN108579744A

  • Catalyst for hydrogen production through ammonia decomposition as well as preparation method and application of catalyst

    CN117065765A

  • Supported cerium-zirconium solid solution photocatalyst, preparation method and application thereof in solar energy storage in dehydrogenation catalytic reaction of organic liquid hydride

    CN118122322A

  • Vehicle-mounted internal and external self-heating type ammonia conversion hydrogen production system and control method thereof

    CN118183622A

  • Method of photodecomposing nitrogen-containing compound

    JP2006182615A